Ovarian clear cell adenocarcinoma: a continuing enigma. Issue 4 (3rd October 2006) - Tan, David S P; Kaye, Stan
Abstract : Ovarian clear cell adenocarcinomas (OCCAs) account for <5% of all ovarian malignancies. Compared to other epithelial ovarian cancer (EOC) subtypes, when at an advanced stage, they are associated with a poorer prognosis and are relatively resistant to conventional platinum-based chemotherapy. By contrast, early-stage clear cell ovarian cancer carries a relatively good prognosis. Hence, there is a need to improve our understanding of its pathobiology in order to optimise currently available treatments and develop new therapeutic strategies. This review summarises the currently available literature regarding the pathogenesis of OCCA, its molecular genetic features and postulated molecular mechanisms that underlie its chemoresistant phenotype. Marked similarities with clear cell carcinomas of the kidney and endometrium have been noted by some investigators, raising interesting possibilities regarding novel therapeutic approaches. Unfortunately, most studies on OCCA have hitherto been hampered by insufficient sample sizes, leaving many key issues unresolved. It is envisaged that in the future, high-resolution genomic and gene-expression microarray studies incorporating larger sample sizes will lead to the characterisation of the key molecular players in OCCA biology, which may potentially lead to the identification of novel targets for therapeutic development.